2014
DOI: 10.1016/j.neuchi.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical neurovascular anastomosis: The example of superficial temporal artery to middle cerebral artery bypass. Technical principles

Abstract: The superficial temporal artery to the middle cerebral artery (STA-MCA) bypass is a good example of cerebrovascular anastomosis. In this article, we describe the different stages of the procedure: patient installation, superficial temporal artery harvesting, recipient artery exposure, microsurgical anastomosis, and closure of the craniotomy. When meticulously performed, with the observance of important details at each stage, this technique offers a high rate of technical success (patency>90%) with a very low m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
0
13
0
7
Order By: Relevance
“…Thines et al . [ 14 ] discussed the role of perfect dural closure to prevent wound complications in the perioperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Thines et al . [ 14 ] discussed the role of perfect dural closure to prevent wound complications in the perioperative period.…”
Section: Discussionmentioning
confidence: 99%
“…For STA-MCA bypass, periadventitial tissue layers of STA are normally kept intact with removing conjunctive and adventitial tissues only within 1 cm of the distal end for anastomosis [30] [2, 31, 32]. In the present study, denervation was achieved by removal adventitia and surrounding fascia at 4-5 cm of the distal end of STA.…”
Section: Discussionmentioning
confidence: 99%
“…Part of the donor vessel under the bone flap was unfolded to fit the bone flap and the dura to reduce the bending. There were 8 patients in the control group in which adventitial and conjunctive tissue were dissected and removed no more than 1 cm from distal end of STA [2]. The patency of anastomosis was determined using intraoperative near-infrared indocyanine green angiography (ICGA).…”
Section: Materilas and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly selected recipient has been an easily accessible distal branch of the MCA (M3 or M4), preferably away from the craniotomy edges, with a large enough caliber matching a donor STA branch and proper wall thickness/ Target versus Nontarget Bypass Katano et al 445 stiffness without atherosclerotic change. 23 In the Visual group of the present study, the surgeons essentially selected the recipient artery in the manner just described during the operation. Peña-Tapia et al 24 reported a contrivance that allowed them to perform a 3-cm craniotomy at exactly the most suitable site with a transparent plastic template indicating a horizontal line as an orbitomeatal line and a 5-cm straight vertical line to mark the target point.…”
Section: Selection Of the Recipient Artery And Postoperative Rcbf Incmentioning
confidence: 99%